Tunable Microscale Porous Systems with Dynamic Liquid Interfaces. Issue 18 (1st February 2018) - Zhan, Kan; Hou, Xu
Abstract: Solid microscale porous material systems have attracted more attention in recent years due to their various potential applications, such as energy source transportations, biomedical devices, wastewater treatments, phase separations, etc. However, such systems are still plagued with many issues including fouling, mechanical fragility, inability to self‐heal, and low recyclability that restrict them for further industrial applications. Dynamic liquid‐based microscale porous material systems, especially porous surfaces and membranes, provide a new opportunity for resolving these issues and possess many benefits, such as antifouling, slippery, transparent, recovery, self‐healing, and recycling properties. This Concept is mainly concerned with how to obtain tunable microscale porous systems with dynamic liquid interfaces, and their applications from the surfaces to membranes. The authors hope this concept will attract interest of scientists in areas related to the rapid development and application of various liquid‐based porous systems. Abstract : Porous systems with a liquid‐liquid interface by capillary force are considered as a significant and promising field in science and industry. Liquid‐based surfaces exhibiting slippery, self‐repairing, antifouling, anti‐ice, and recovery properties can be utilized in transporting water, oil, and preventing ice adhesion, etc. Liquid‐based membranes with degassing, anti‐fouling, oil‐water separation, and recovery performances can be used to selectively multiphase separate, easy‐clean, etc.